Signalling of multiple interleukin (IL)‐17 family cytokines via IL‐17 receptor A drives psoriasis‐related inflammatory pathways. (1st September 2021) - Tollenaere, M.A.X.; Hebsgaard, J.; Ewald, D.A.; Lovato, P.; Garcet, S.; Li, X.; Pilger, S.D.; Tiirikainen, M.L.; Bertelsen, M.; Krueger, J.G.; Norsgaard, H.
Summary: Background: The interleukin (IL)‐23/IL‐17 immune axis is of central importance in psoriasis. However, the impact of IL‐17 family cytokines other than IL‐17A in psoriasis has not been fully established. Objectives: To elucidate the contribution of IL‐17 family cytokines in psoriasis. Methods: To address the expression and localization of IL‐17 family cytokines, lesional and nonlesional skin samples from patients with psoriasis were analysed by several complementary methods, including quantitative polymerase chain reaction, immunoassays, in situ hybridization and immunohistochemistry. Mechanistic studies assessing the functional activity of IL‐17 family cytokines were performed using ex vivo cultured human skin biopsies and primary human keratinocytes. Results: We demonstrated that IL‐17A, IL‐17F, IL‐17A/F and IL‐17C are expressed at increased levels in psoriasis lesional skin and induce overlapping gene expression responses in ex vivo cultured human skin that correlate with the transcriptomic signature of psoriasis skin. Furthermore, we showed that brodalumab, in contrast to ixekizumab, normalizes gene expression responses induced by the combination of IL‐17A, IL‐17F, IL‐17A/F and IL‐17C in human keratinocytes. Conclusions: Several IL‐17 ligands signalling through IL‐17RA are overexpressed in psoriasis skin and induce similar psoriasis‐related inflammatory pathways demonstrating their relevance in relation to therapeutic intervention in psoriasis.